HEALTH CARE EXCESSES ISSUE ACTION PLAN: BACKGROUND (Tufts Archival Research Center, 2007)
Action Plan regarding strategies to oppose tobacco restrictions, bans and cigarette tax increases. Describes the efforts of the anti-smoking advocacy to push a social agenda as well as the use of cigarette tax increases to fund health care costs. Details the plan to create a $1 increase on price of cigarette packs. Mentions the issue of health care costs as a platform for the Clinton campaign and the role of the cigarette tax to covering these costs. Highlights the importance of using health care excesses to combat the arguments of the anti-smoking advocates.